EVALUATION OF JUNIOR HIGH SCHOOL TEACHER CERTIFICATION POLICY IMPLEMENTATION IN BOGOR DISTRICT EDUCATION OFFICE - GUNAWATI, LITA (PPs UNJ, 2016)
The objective of this research was to evaluate the implementation of junior high school teacher certification policies in Bogor District Education Office. This evaluation research used a qualitative approach with CIPP evaluation model. The data in this research was got through interview, observation, and documentation study. Data analysis conclude that, (1) the purpose of certification is defined well, possess a time limit, operated, and understood well, (2) planning and allocation of resources have been classified properly, according to sources, the allocation of funds, execution time, as well as performance indicators, (3) the implementation of the certification process has followed the guidelines of the central (4) performance of professional teachers have the ability to plan a good learning, manage and evaluate student learning. Welfare certified teacher can only meet primary needs, not the needs of secondary and so forth. Recommendations are given is the purpose of certification should be specified achievement standards to be more objective, transparent and accountable, the need for good cooperation in development and teacher professional development, as well as more transparency in the socialization of policies on equality of civil servants and non-civil servant teachers.